Low-cost Gent type sampler constructed for urban atmospheric aerosol sampling - Franzin, Bruno Trevizan [UNESP]; Hojo, Ossamu [UNESP]; Ferreira, Maicon Roberto [UNESP]; Forti, Maria Cristina; Meneghetti, Carlos Daniel; de Marchi, Mary Rosa Rodrigues [UNESP]; de Oliveira, Cristina Maria Roque Ramiro; Fertonani, Fernando Luis [UNESP] (Springer Nature, 2021)
The importance of studying the atmospheric pollution due to its effects on human health and other ecosystems, the inexistence of national production of equipment for air sample collection, and the high cost of the imported equipment (especially in developing countries) led the authors of the present work to construct a low-cost Gent type sampler. The construction of the sampler was carried out by combining low-cost materials with good mechanical strength (such as nylon 6.0), hydraulic piping PVC, and the use of a 3D printer. The innovation of the present work is the employment of a 3D printer using ABS polymer to create the grids that cannot be machined. In addition to the sampler, the system is composed of a vacuum pump, a gas meter, and a rotameter. The total cost of the sampling system amounted at about 1200 USD, and the cost of the manufactured Gent type sampler did not reach 100 USD. The results obtained while using this set for sampling atmospheric aerosol for a period of 11 months were compared with the mass concentration of PM10 obtained from the official environmental company, CETESB of São Paulo State, Brazil, showing good correlation with those from CETESB — which confirmed its effectiveness and suitability for use. The low cost, easy operation, and versatility of the built Gent type sampler enable its use for scientific and academic purposes. The equipment can be useful in environmental monitoring networks, in low-income regions, and as an instrument for environmental education used in universities. Graphical abstract: [Figure not available: see fulltext.].
Keywords: 3D print; Environmental chemistry; Gent type sampler; Low-cost sampler construction; PM10 concentration; SFU